Systematic Review on New Challenges of University Education Today: Innovation in the Educational Response and Teaching Perspective on Students with Disabilities - María Dolores Pérez-Esteban; Jose Juan Carrión-Martínez; Luis Ortiz Jiménez (Social Sciences, 2023)
Offering a suitable educational response to students with disabilities continues to be a challenge for higher education institutions, where the teaching attitude, the educational strategies to deal with diversity and the obstacles or difficulties continue to condition the commitment to inclusive education at universities. This systematic review has been carried out following the indications of the PRISMA method. The main objective is to present critical information about the educational response offered to students with disabilities at higher education institutions. Fourteen articles dealing with teaching attitude, difficulties and strategies used were reviewed. The results show how there is a positive attitude towards students with disabilities in some areas, various inclusive strategies are established in the classroom and there are still obstacles that make it difficult to meet all students’ needs. In conclusion, inclusive education continues to be a pending issue for university institutions, which are moving towards inclusion, yet at a slower pace, in comparison to other education levels.